A Pharmaceutical Standardization of Guduchi (Tinospora cordifolia) (International Journal of Ayurveda and Pharma Research, 2023)
Guduchi, scientifically known as Tinospora cordifolia, is a prominent herb in Ayurveda and traditional medicine systems. Its rich history of use for centuries, is owing to its composite therapeutic properties. This botanical has gained increasing attention in modern medicine due to its potential as an immunomodulatory, anti-inflammatory, antioxidant and adaptogenic agent. This abstract focuses on the standardization of Guduchi to ensure consistent quality and potency in herbal formulations. Standardization involves the quantification of key bioactive compounds, such as alkaloids, glycosides and polysaccharides, which contribute to its therapeutic effects. For the identification, purity and strength these must be fulfilled - analytical parameters like foreign matter, total ash value, acid insoluble ash, alcohol soluble extractive, water soluble extractive and moisture content in fresh drug. Overall, no adverse reactions or toxicity of Guduchi have been obtained. The present study was focused on analytical studies which was carried out separately on the basis of classically illustrated organoleptic tests, modern physio-chemical parameters like loss on drying at 110°C, ash value, acid insoluble ash, alcohol soluble extract, pH (10% aqueous solution), water soluble extractive in different parameters and microscopic study of Guduchi powder. Hence the present work may be used for the quality assessment and standardization of Guduchi (Tinospora cordifolia).